O Discurso de professores de prática de ensino e a perspectiva da etnomatemática - Campos, Elza da Silva (2006)
This research has as objective to understand the speeches of Mathematic's Practice teachers of License Course in Mathematics, considering the concepts of Teaching Practice and of Ethnomathematics and how it has been your actuation and which perspectives are more valued in this matter's development. Trying to find the answers for our questions from the date colecting together seven Public and Private Universiy's Teaching Practice Teachers, it intended explanis its Teaching Practices perspectives and check if its contains Ethnomathematics's elements. In order to reach the proposal objective, it used in its methodology, the foresee of qualitative approach in Education and the interview as the methodological procedure with Trainer's teachers of Mathematic's Teaching. It also provides the study of the Dossie of The National Laws concerned to the Basic Education Teaching Teachers. The results showed that these teachers Performance Work Teaching Practice concerning in Ethnomathematics. Considering the Teacher Work's conditions and the point of the teachers be researchers, having flair to Ethnomathematics Work Trend